2008
DOI: 10.1063/1.2856528
|View full text |Cite
|
Sign up to set email alerts
|

Resonant pumping in a multilayer impedance pump

Abstract: This paper introduces the concept of multilayer impedance pump, a novel pumping mechanism inspired by the embryonic heart structure. The pump is a composite two-layer fluid-filled elastic tube featuring a thick gelatinous internal. Pumping is based on the impedance pumping mechanism. In an impedance pump, elastic waves are generated upon external periodic compressions of the elastic tube. These waves propagate along the tube's walls, reflect at the tube's extremities, and drive the flow in a preferential direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…The thick gelatinous layer was found to amplify the elastic waves responsible for Liebau effect-driven pumping, so that only small excitations of the active compression side (10% external radius) were needed to produce significant flow (Loumes et al, 2008). The presence of a thick layer of cardiac jelly obviously seems to be advantageous for the pumping function of both kinds of tubular hearts; those working as peristaltic pumps (Barry, 1948) as well as those working as Liebau pumps (Loumes et al, 2008). Therefore, the presence of a thick layer of cardiac jelly cannot be regarded as supporting evidence for either of the two competing theories of early cardiac pumping mechanism.…”
Section: Solid (Morphological) Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thick gelatinous layer was found to amplify the elastic waves responsible for Liebau effect-driven pumping, so that only small excitations of the active compression side (10% external radius) were needed to produce significant flow (Loumes et al, 2008). The presence of a thick layer of cardiac jelly obviously seems to be advantageous for the pumping function of both kinds of tubular hearts; those working as peristaltic pumps (Barry, 1948) as well as those working as Liebau pumps (Loumes et al, 2008). Therefore, the presence of a thick layer of cardiac jelly cannot be regarded as supporting evidence for either of the two competing theories of early cardiac pumping mechanism.…”
Section: Solid (Morphological) Dynamicsmentioning
confidence: 99%
“…However, recent studies on Liebau pumps have shown that this must not be the case. Inspired by the multilayered structure of embryonic heart tubes, engineers have constructed a multilayered Liebau pump in which a thick gelatinous layer acts as cardiac jelly (Loumes et al, 2008). The thick gelatinous layer was found to amplify the elastic waves responsible for Liebau effect-driven pumping, so that only small excitations of the active compression side (10% external radius) were needed to produce significant flow (Loumes et al, 2008).…”
Section: Solid (Morphological) Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further study of the pumping power transferred to the fluid by the elastic tube, an energy calculation was performed based on the method described in Loumes, Avrahami & Gharib (2008). The control volume (∀) selected for the calculation is defined as the long passive region (illustrated in figure 13a), bounded by the elastic tube and the cross-sections z = 4 cm (input) and z = 14 cm (output).…”
Section: P-q Loops As Indication Of Energy Transformmentioning
confidence: 99%
“…The input and output energy fluxes through the control surface were calculated from their kinetic and potential components (for further details refer to Loumes et al 2008):…”
Section: P-q Loops As Indication Of Energy Transformmentioning
confidence: 99%